A Critical Analysis of the Perioperative Management of Patients with Ehlers Danlos Type IV (Vascular) Syndrome. Issue 9 (September 2017) - Martin, J
This paper discusses the perioperative care needs of patients with Ehlers Danlos type IV (vascular) syndrome. Ehlers Danlos syndrome (EDS) is a heritable group of connective tissue disorders characterised by varying degrees of tissue, blood vessel and internal organ fragility as well as skin and joint hypermobility (De Paepe & Malfait 2012). In 1997 EDS was revised and classified into six subtypes: classical (Types I and II), hypermobility, vascular (Type IV), kyphoscoliosis and arthrochalasia type. Each classification has been based on the following aspects: diagnostic uniformity, natural history, management, genetics, and the identification of potential areas for research (Beighton et al 1998). Vascular type EDS has serious implications for any form of surgical procedure and it is therefore imperative that theatre staff are fully conversant with the needs of this patient group. Overall awareness needs to be increased, particularly as most patients will most frequently be seen in an emergency situation, as elective procedures are avoided as far as possible.